Cytotoxicity and DNA damage of a panel of manufactured nanomaterials in rat alveolar epithelial RLE-6TN cells - Brandão, Fátima (2019)
Main goal: The aim of this study was to evaluate the cyto- and genotoxicity of a panel of MNMs, including SiO2 NPs, graphene oxide, and nano-sized pigments in rat alveolar epithelial cells (RLE-6TN), a primary target following inhalation exposure.